Pazopanib in Metastatic Renal Cancer: A “Real-World” Experience at National Cancer Institute “Fondazione G. Pascale” - Cecere, Sabrina C.; Rossetti, Sabrina; Cavaliere, Carla; Della Pepa, Chiara; Di Napoli, Marilena; Crispo, Anna; Iovane, Gelsomina; Piscitelli, Raffaele; Sorrentino, Domenico; Ciliberto, Gennaro; Maiolino, Piera; Muto, Paolo; et al. (Frontiers in Pharmacology, 2016)
Pazopanib is an oral angiogenesis inhibitor, currently approved for treatment of metastatic renal cell carcinoma (mRCC) and soft tissue sarcoma. The present study analyzed the outcomes of pazopanib in first-line treatment of mRCC, in a single Italian cancer center. In the light of the retrospective, observational nature and the unselected population, our experience can be defined a “real-world” study. The medical records of 38 mRCC patients treated with front-line pazopanib were retrospectively reviewed and analyzed. The progression free survival (PFS) and the overall survival (OS) were the primary endpoints, while secondary objectives included Objective Response Rate (ORR), Disease Control Rate (DCR), and treatment tolerability. Pazopanib achieved a median PFS (mPFS) of 12.7 months (95% CI, 6.9-18.5 months). The median OS (mOS) was 26.2 months (95% CI, 12.6-39.9 months); the observed ORR and DCR were 30.3% and 72.7%, respectively, with a median duration of response of 11 weeks. mPFS appeared not to be influenced by number of co-morbidities (<3 vs >3), gender, Fuhrman grade and age. Conversely, the ORR and the DCR positively affect the mPFS (HR=0.05 [95% CI, 0.05-055], p=0.01; HR=0.10 [95% CI, 0.02-0.43], p=0.002 respectively). A worse outcome was associated with a lower mPFS in patients with liver metastases (p= 0.2) and with a high tumor burden (number of metastatic sites <6 vs >6) (p= 0.08). Worst OS was observed in patients age >70 years old (HR=6.91 [95% CI, 1.49-31.91], p=0.01). The treatment was well tolerated: no grade 4 adverse events, nor discontinuation due to toxicities was reported. Grade 3 hypertension affected positively the OS reaching the statistical significance (HR=0.22 [95% CI, 0.05-0.8], p=0.03) and thyroid dysfunction (hypo and hyperthyroidism) seems to correlate with better outcome in terms of a longer mPFS (HR=0.12 [95% CI, 0.02-0.78], p=0.02). Our results are consistent with those reported in prospective phase III trials and the published retrospective “real world” experiences. This analysis confirms the safety and efficacy of pazopanib in first-line setting, both in frail patients with multiple co-morbidities and Karnofsky PS <80% and in younger, healthier patients with a number of metastatic sites < 6. Keywords mRCC, first-line, pazopanib, real-life, PFS